Entorno tecnológico y socioeconómico de la habichuela larga en el Caribe Húmedo de Colombia - Martínez Reina, Antonio María; Tordecilla Zumaqué, Lilibet; Cordero Cordero, Carina Cecilia; Grandett Martínez, Liliana María (Universidad Pedagógica y Tecnológica de Colombia, 2019)
1 recurso en línea (página 7-27)